Does sunscreen use comply with official recommendations?: Results of a nationwide survey in Germany - Görig, Tatiana; Schneider, Sven; Seuffert, S.; Greinert, R.; Diehl, Katharina (Journal of the European Academy of Dermatology and Venereology, 2020)
Background - The use of sunscreen can reduce the risk of UV‐induced skin lesions. Health authorities have provided recommendations for the correct use of sunscreen use: Sufficient amount of sunscreen should be applied at least 30 min before the sun exposure and should be reapplied every 2 h.